2020
DOI: 10.1002/adfm.202002486
|View full text |Cite
|
Sign up to set email alerts
|

Multiarray Nanopattern Electronic Nose (E‐Nose) by High‐Resolution Top‐Down Nanolithography

Abstract: An electronic nose (E‐nose) is an artificial sensing device that mimics the human olfactory system using a multiarray sensor system. However, since the design and fabrication of multiarray sensing channels are significantly limited because of the requirement of time‐consuming and nonuniversal processes, the development of commercializable and high‐throughput fabrication approaches are critically required. Herein, high‐resolution top‐down lithography is developed for E‐nose fabrication for the first time. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Particularly, semiconductor-based gas sensors have been broadly studied due to clear working principles, simple device structure, and good response activity to toxic gases [5,6]. Typical semiconductor gas sensors are manufactured via complex stepwise photolithography processes [7,8]. Although the traditional fabrication process ensures massive wafer-scale productivity, this method cannot meet small-volume and on-demand capacities.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, semiconductor-based gas sensors have been broadly studied due to clear working principles, simple device structure, and good response activity to toxic gases [5,6]. Typical semiconductor gas sensors are manufactured via complex stepwise photolithography processes [7,8]. Although the traditional fabrication process ensures massive wafer-scale productivity, this method cannot meet small-volume and on-demand capacities.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Persistent efforts have been devoted to addressing the selectivity issue, a prerequisite for the real applications of MOS sensors. [4][5][6] Normally, it is difficult to discriminate adsorbed molecules using a single MOS sensor operated at isothermal (constant operation temperature) measurements, because of the limited extracted features (i.e., temperature-dependent sensitivity [7] and adsorption/desorption time [8] ), especially for chemically and structurally similar VOCs molecules, which possess similar (reducing vapors) electrical responses. [9] Constructing electronic nose or sensor arrays with distinct surface properties by adopting new materials, extrinsic doping, [10] noble metal modification, [11] and heterogenous or composite materials [12] has been widely used to multiply the (isothermal) features, thus enriching the recognition capability of MOS sensors.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Various n-type (SnO 2 , [15] ZnO, [16,17] WO 3 , [18] In 2 O 3 [19] ) based electronic noses have been reported. For example, Kang et al [7] fabricated electronic noses with five different MOS sensors through high-resolution nanolithography and successfully distinguished seven types of hazardous vapor. Shi et al [13] reported the precise discrimination of similar (mesitylene, o-xylene, and toluene) vapors using cross-reactive arrays.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor sensors were usually operated at an elevated (isothermal) temperature to observe a clear resistance/conductance variation upon exposure to target molecules; isothermal sensitivity was typically extracted as one “feature” of target molecules. Resembling with face/fingerprint recognition, extracting sufficient features of target molecules from electrical response signals is necessary. , Modifying the surface properties of sensors by doping, , decoration, , or hybridization offers an apparent approach of expanding features of target molecules by constructing sensor arrays. Wang et al reported an efficient approach to extract molecule features by analyzing multiple field-effect transistor (FET) characteristics of an ambipolar diketopyrrolopyrrole (DPP) copolymer sensor, and discrimination of three xylene isomers (a fixed concentration of 40 ppm in the inert N 2 background) was first demonstrated . However, insufficient stabilities in the structure (i.e., swelling) and electrical properties of DPP in the ambient air atmosphere hinder its practical applications .…”
mentioning
confidence: 99%